Prevalence of Occult Hepatitis C Virus Infection in Hemodialysis Patients - Masomeh Bayani; Mohammad Reza Hasanjani Roushan; Mohammad Jafar Soleimani Amiri; Yousef Yahyapour; Soheil Ebrahimpour; Somayeh Akbarzadeh Jelodar (Babol University of Medical Sciences, 2021)
Background: Via hemodialysis, viral infections can be transmitted in patients a new definition of this infection with no increase in liver enzymes, negative HCV-PCR in serum and presence of virus in the liver and peripheral blood mononuclear cell (PBMC) called occult hepatitis C virus (HCV) infection (OCI). We decided to examine the prevalence of occult hepatitis C infection on hemodialysis cases. Methods: The current research is a cross-sectional study on patients with end-stage renal disease (ESRD) who were at three hemodialysis centers in Mazandaran province in Iran during 2012-2014. In this study of 356 patients who were undergoing hemodialysis, 54 patients were excluded due to positive HCV Ab, and the remaining 302 patients were enrolled. The test of all serum samples for HCV-RNA detection of plasma and PBMCs was done by real-time polymerase chain reaction (real-time PCR). Results: There was a significant association between the duration of dialysis with the prevalence of occult HCV infection (P=0.017). Eight (2.65%) patients were positive for HBs Ag and with OCI, but none of them was infected with both hepatitis C and B obviously. Also among the total number of patients, nine patients tested positive for HCV RT-PCR in PBMC in which one of them was positive for serum HCV RNA PCR and was excluded from the study. Conclusion: The results showed that eight patients had an OCI. There was not any association found between age and sex with OCI, but there was a significant relationship between the duration of dialysis with the prevalence of OCI.